Design and development of autonomous omni-directional mobile robot with mecanum wheel - Jefri Effendi Mohd Salih (Universiti Malaysia Perlis, 2008)
A variety of designs of mobile robot have been developed in recent years in order to improve their omni-directional maneuver and practical applications. Omni-directional mobile robot has vast advantages over conventional design likes differential drive in term of mobility in congested environments. The main purpose of this research is to design, develop and implement an omni-directional mobile robot with custom made mecanum wheel for autonomous navigation. Using these mecanum wheels, the mobile robot is provided with three degree of freedom (DOF) mobility. Attention also paid for the development of kinematics and dynamics model to analyze the mobile platform motion performances. Motor driver and robot controller were also developed. Motion control algorithm using BasicStamp Editor software was developed to test the capabilities of the system’s mobility performance. Experiments were performed to analyze the motion characteristic of the mobile robot motion in Y axis, X axis and differential drive capabilities. Using ultrasonic and line follower sensors, basic autonomous navigation had been develop and tested. Based on the experiment conducted, the autonomous navigation gave satisfactory result. The developed mobile robot will provide a test bed for advanced path planning and navigation projects in the future.